2022
DOI: 10.1177/20595131221134052
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation for modulation of neuropathic pain and improvement of scar tissue

Abstract: Background This case-report explores the effects of photobiomodulation therapy (PBMT) on the healing of scar tissue. The patient was a 32-year old female two years post cholecystectomy resulting in a 15 cm linear scar that was causing severe pain. Methods Treatment was initiated using the BIOFLEX® therapist device which consists of LED arrays and laser probes of a specific wavelength, power and frequency applied directly on the skin overlying the scar. The frequency and duration of treatment was every other da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As a result, the downregulation of TGF-b1 by PBMT affects the reduction and inhibition of profibrotic gene synthesis and collagen synthesis. These are likely to indicate the suppression of wound tissue scarring [42,43]. On the other hand, TGF-b1 is a potent regulator of inflammatory responses and is usually upregulated in the early phase of wound healing.…”
Section: Preventive Effect Of Pbmt On Scarringmentioning
confidence: 99%
“…As a result, the downregulation of TGF-b1 by PBMT affects the reduction and inhibition of profibrotic gene synthesis and collagen synthesis. These are likely to indicate the suppression of wound tissue scarring [42,43]. On the other hand, TGF-b1 is a potent regulator of inflammatory responses and is usually upregulated in the early phase of wound healing.…”
Section: Preventive Effect Of Pbmt On Scarringmentioning
confidence: 99%
“…Photobiomodulation (PBM), also known as low-level light therapy, is a non-invasive technique that uses lasers or light-emitting diodes (LEDs) with low-level light in the visible and near-infrared (NIR) spectra to regulate biological processes [17,18]. PBM research is being conducted worldwide and has already been shown to be effective in clinical applications, such as tissue repair or pain relief, and in various medical applications including sports medicine [19][20][21][22][23][24][25]. PBM is thought to enhance cellular metabolism and other processes, eventually leading to increased cell proliferation and differentiation [26].…”
Section: Introductionmentioning
confidence: 99%